Annotated Distribution Records for Kentucky Mollusca - Branley A. Branson; Donald L. Batch (Hello World!, 1971)
In the annotated list which follows, the numbers of specimens collected at each locality are given first and the collecting station number follows in parentheses. All measurements are in millimeters.